2019
DOI: 10.2134/jeq2018.11.0417
|View full text |Cite
|
Sign up to set email alerts
|

Fall Tillage Reduced Nutrient Loads from Liquid Manure Application during the Freezing Season

Abstract: Abbreviations: CT, fall tillage with a chisel plow and spring finisher; CT-C, fall tillage and unmanured control treatment; CT-D, fall tillage treatment with December manure application timing; CT-J, fall tillage treatment with January manure application

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 44 publications
3
30
1
Order By: Relevance
“…Conversely, results from Stock et al. (2019) and the current study found manure application to unfrozen soils in the fall reduced losses of nutrients. In the current study, post‐graze simulations were not able to occur until after snowmelt had occurred for logistical and safety reasons.…”
Section: Discussioncontrasting
confidence: 75%
“…Conversely, results from Stock et al. (2019) and the current study found manure application to unfrozen soils in the fall reduced losses of nutrients. In the current study, post‐graze simulations were not able to occur until after snowmelt had occurred for logistical and safety reasons.…”
Section: Discussioncontrasting
confidence: 75%
“…Overall, during the nongrowing season and early growing season of cold climates, actual evapotranspiration is low and the precipitation/evapotranspiration ratio is relatively high, resulting in high runoff potential. This can elevate the risk of nutrient losses in cold climates, particularly when there is a supply of nutrients from sources such as fertilizer, manure (Stock et al, 2019; Vadas et al, 2019), plant materials (Costa et al, 2019; Liu et al, 2019b), and surface soils (Liu et al, 2019a; Wilson et al, 2019b).…”
Section: Agronomic Biogeochemical and Hydrological Characteristics mentioning
confidence: 99%
“…Our objectives were (i) to describe how manure application timing and runoff hydrology control dissolved P concentrations in runoff from field plots receiving liquid dairy manure, and (ii) to determine if the SurPhos manure P runoff simulation model (Vadas et al, 2007) can reliably predict dissolved P concentrations in runoff for the experimental winter conditions. Stock et al (2019a) describe the approach used in the field study and the effects of application timing and tillage on nutrient runoff loads (kg ha −1 ). This paper focuses on dissolved P runoff concentrations to better understand and model P runoff dynamics as a function of source (P available in manure) and hydrology (both the rain and snowmelt water that mobilizes available manure P and the percentage of this water that becomes runoff ).…”
Section: Dynamics Of Measured and Simulated Dissolved Phosphorus In Runoff From Winter-applied Dairy Manurementioning
confidence: 99%